Gender determination by morphometric analysis of mandibular ramus in sriganganagar population: A digital panoramic study - Saloni; Pradhuman Verma; Princy Mahajan; Ankush Puri; Sukhleen Kaur; Sakshi Mehta (Wolters Kluwer Medknow Publications, 2020)
Background: Mandible is a dimorphic, dense compact bone that makes it very durable and well preserved in mass disasters for personnel identification. Mandibular ramus morphometric measurements can be used for gender determination using orthopantomogram (OPG) or on dry mandibles. Aim: To determine gender from morphometric analysis of mandibular ramus of 200 digital OPG of patients from Sriganganagar population. Materials and Methods: The study was conducted on randomly selected digital OPG of 200 patients of both genders between the ages of 21 and 70 years taken using CS8000C machine from daily OPD. Morphometric analysis of mandibular ramus (maximum ramus breadth, minimum ramus breadth, condylar height, projective height of ramus, and coronoid height) was done twice by single maxillofacial radiologist independently at an interval of 1 day and mean of both the values were considered. The collected data was tabulated and analyzed using SPSS Software version 20 using independent ṯ-test and discriminant function analysis. Results: Out of total 200 subjects, 37% were male and 63% were female. Mean of minimum ramus breadth, maximum ramus height, and projected ramus height was noted significantly more among males while maximum ramus breadth was noted slightly higher in females. The overall accuracy for determining sex from mandibular ramus was found to be 77.6%, whereas for determining male and female, the accuracy was 78.4% and 76.8%, respectively. Conclusion: Mandibular ramus can be used for sexual dimorphism by morphometric analysis done on OPG among Sriganganagar population.